Big data analysis of foreign exchange rates among Japan, South Korea and Taiwan. (2017) - Lee, Yao-Hsien; Wang, Yi-Hsien; Lee, Mei-Yu
This paper models foreign exchange rates among the Japanese yen (JPY), the South Korean won (KRW) and the Taiwan dollar (TWD). We select open data from the CMoney database that total 17, 349 data points and use big data analysis to establish the probability distributions of foreign exchange rates of three countries. The first finding is that the TWD rate is more stable than the JPY rate and the KRW rate, and it is fixed a specific rate with 39.83% probability. The second finding is that the effect of the JPY rate on the TWD rate is not equivalent to the effect of the KRW rate.